1993
DOI: 10.1620/tjem.170.35
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of CT Scan in Malignant Glioma.

Abstract: In 91 malignant gliomas treated with radiation therapy, CT scan which was taken before treatment was reviewed to examine the significance as a prognostic indicator. The irradiation methods and the surgical resectability did not affect the survival. Similarly, the tumor location and the grade of the low density area (LDA) surrounding the contrast enhanced area (CEA) had no significance on the prognosis. As a result of the multi-variate analysis, the histopathologic diagnosis, the CEA size and the CEA pattern we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Wood et al 72 found no relationship between preoperative tumor size and survival, nor did Miller et al, 50 or Shibamoto et al 77 The same was observed by Simpson et al, 51 Wuerschmidt et al, 29 Kowalczuk et al, 46 Kreth et al, 47 and Hulshof et al 48 Some of these studies did not use size, but rather tumor volume. 46,50 Contrary to that, Reeves and Marks 78 observed its significant prognostic value in glioblastomas, as did Yamada et al 53 and Jeremic et al 25 in malignant glioma. There are numerous explanations for such discrepancy, including the small number of patients evaluated, rapid tumor growth immediately prior to presentation 79 leading to a short time it takes for the tumor to grow from a lesion of a small size to a large size when compared to the overall time from diagnosis to death, less importance of the size than the location of the tumor, 80,81 as well as the fact that the effect of treatment received after the initial scan outweighs any that preoperative tumor size may have.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Wood et al 72 found no relationship between preoperative tumor size and survival, nor did Miller et al, 50 or Shibamoto et al 77 The same was observed by Simpson et al, 51 Wuerschmidt et al, 29 Kowalczuk et al, 46 Kreth et al, 47 and Hulshof et al 48 Some of these studies did not use size, but rather tumor volume. 46,50 Contrary to that, Reeves and Marks 78 observed its significant prognostic value in glioblastomas, as did Yamada et al 53 and Jeremic et al 25 in malignant glioma. There are numerous explanations for such discrepancy, including the small number of patients evaluated, rapid tumor growth immediately prior to presentation 79 leading to a short time it takes for the tumor to grow from a lesion of a small size to a large size when compared to the overall time from diagnosis to death, less importance of the size than the location of the tumor, 80,81 as well as the fact that the effect of treatment received after the initial scan outweighs any that preoperative tumor size may have.…”
Section: Discussionmentioning
confidence: 90%
“…52 Results, here as well, are conflicting. Although some 24,25,29,46,47,50,52,53,75 did not observe its influence on treatment outcome, others did. Gehan and Walker 82 observed inferior survival for parietal location, and Simpson et al 51 and Curran et al 70 found independent influence of frontal tumor location, as we did.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A significant part of the power of the model is the use of the actual sizes shown in the MRIs (Figure 2). The prognostic importance of the 'size' has also been controversial, a few (Yamada et al, 1993;Xue and Albright, 1999;Jeremic et al, 2004) reporting it to be significant but most (Reeves and Marks, 1979;Andreou et al, 1983;Wood et al, 1988;Hammoud et al, 1996;Kowalczuk et al, 1997;Keles et al, 1999;Kreth et al, 1999;Lacroix et al, 2001) failing to find any relation. Xue and Albright (1999) make the point that the volume should be calculated as accurately as possible (i.e., planimetrically as the sum of the areas), as we have done, not modelled simply as spheres or ellipsoids with only the diameter(s) measured.…”
Section: Discussionmentioning
confidence: 99%